Assessing Undergraduate Students' e-Learning Competencies: A Case Study of Higher Education Context in Indonesia - Ati Suci Dian Martha; Kasiyah Junus; Harry Budi Santoso; Heru Suhartanto (MDPI AG, 2021)
The COVID-19 pandemic that occurred in early 2020 around the world has implications for Indonesia's education sector. This pandemic led to the Indonesian government policy to study from home at all academic levels using a distance learning approach. Studies on e-learning preparedness in Indonesia involving more comprehensive samples of universities during the pandemic are still limited. This study extended samples from several public and private universities in Indonesia to get a broader picture of e-learning readiness in various faculties with diverse university online learning cultures. This study used Rasch analysis to determine the validity and reliability of the instrument and differential item functioning (DIF) analysis to identify responses based on students' demographic profiles. The results show that most students were ready to study online, but a few were not ready. Moreover, the results show significant differences in students' e-learning readiness based on the academic year at university, the field of study, the level of organizational e-learning culture of the university, gender, and region. This work provides an insight into student readiness to study online, especially in higher education in Indonesia. The article presents the implications of online learning practices in universities and recommendations for future e-learning research.